PENGARUH PENGGUNAAN MODEL CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR IPA DI SEKOLAH DASAR - Duri, Rapika; F, Farida; mansurdin, mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This study aims to determine the effect of using Contextual Teaching and Learning method on students learning outcome of V grades Science class. Type og the research is experiment with quasi experiment method in the form pretest-posttest non-equivalent group. The samples of the research are 30 students of SD 12 Bukit Cangang from class V as a experiment class and 30 students of SDN 01 Benteng Pasar Atas from class VB as a control class which are selected based on simple random sampling technique. Based on t-test calculation obtained t calculate 2,09, while ttabel at level of trust 0,05 is 1,67155, so thitung > ttabel. This means that CTL model better in Science lesson. Keywords: CTL model, Science learning outcome.